Analisis Pengaruh Brand Image, Perceived Quality, dan Resale Value Terhadap Kepuasan Serta Loyalitas Konsumen Produk Otomotif China dan Jepang di Indonesia - Harimurti, Panji Satria; Indriani, Farida (Faculty of Economics and Business | Universitas Diponegoro, 2023)
The purpose of this study is to analyze the factors that cause consumer satisfaction and loyalty to Japanese brands in Indonesia to be very high, thus causing the dominance of sales explained before. In addition, this study also analyzes the factors that cause sales of Chinese brand cars to lag behind Japanese brand cars, how to take the right steps to increase satisfaction and loyalty to Chinese brand consumers in Indonesia, and to compare the level of brand image, perceived quality, resale value, consumer satisfaction, and consumer loyalty between both of them. The population used in this study are Indonesian people who have private four-wheeled vehicles with brands originating from Japan or China. The number of respondents in this study amounted to 240, with the data collection method done through a questionnaire. The analysis in this study was carried out using the SPSS analysis tool. The results of the study indicate the fact that the factors that influence the dominance of Japanese brand sales in Indonesia for many years are the perception of product quality and consumer satisfaction. In addition, the factors that cause the Chinese car products to be less attractive in Indonesia than Japanese cars come from its brand image and consumer satisfaction. After testing the hypothesis, it can be concluded that to increase consumer satisfaction of Chinese brand cars in Indonesia is to focus on marketing strategies to improve brand image and perception of product quality, while increasing consumer loyalty can be done by implementing marketing strategies that focus on increasing product resale value and customer satisfaction. Finally, the results of the independent-t-test state that there are significant differences between brand image, perceived quality, customer satisfaction, and consumer loyalty between Chinese and Japanese brand cars in Indonesia.